INCIDENCE, RISK FACTORS, AND SEQUELAE OF POST-KIDNEY TRANSPLANT DELIRIUM. (11th November 2018) - McAdams-Demarco, M; Haugen, C; Warsame, F; Bae, S; Neufeld, K; Brown IV, C; Carlson, M; Segev, D
Abstract: Delirium is the acute decline and fluctuation in cognitive function following a stressor like surgery. Frail kidney transplant (KT) recipients may be particularly vulnerable to surgical stressors resulting in delirium and subsequent adverse outcomes. We sought to identify the incidence, risk factors, and sequelae of post-KT delirium. We studied 125, 304 KT recipients (1999–2014) to estimate delirium incidence in national registry claims. Additionally, we used a validated chart-abstraction algorithm to identify post-KT delirium in 893 KT recipients (2009–2017) from a cohort study of frailty. Delirium risk factors were identified using adjusted logistic regression. Delirium sequelae were identified using adjusted logistic regression (length of stay [LOS]≥2weeks and institutional discharge [skilled nursing facility or rehabilitation facility]) and adjusted Cox regression (death censored graft loss and mortality). Only 0.8% of KT recipients had a delirium claim. In the cohort study, delirium incidence increased with age (18–49:2.0%; 50–65:4.6%; 65–75:9.2%; and ≥75:13.8%) and frailty (9.0% vs. 3.9%;p=0.01); 20.0% of frail recipients aged≥75 experienced delirium. Frailty was independently associated with delirium (OR=2.05; 95%CI:1.02–4.13, p=0.04) but pre-morbid global cognitive function was not. Recipients with delirium were at an increased risk of ≥2 week LOS (OR=5.42;95%CI:2.76–10.66, p<0.001), institutional discharge (OR=22.41;95%CI:7.85–63.98, p<0.001), graft loss (HR=2.73;95% CI:1.14–6.53, p=0.025), and mortality (HR=3.12;95%CI:1.76–5.54, p<0.001). Post-KT delirium is a strong risk factor for subsequent adverse outcomes, yet it is a clinical entity that is often missed. Older and frail recipients are uniquely vulnerable to delirium. Transplant centers should be aware of the risks associated with post-KT delirium and implement interventions to reduce delirium risk.